2013
DOI: 10.1186/1750-1172-8-88
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of alpha mannosidosis a longitudinal study

Abstract: BackgroundAlpha-Mannosidosis is a rare lysosomal storage disorder, caused by the deficiency of the enzyme alpha-Mannosidase. Clinically it is characterized by hearing impairment, skeletal and neurological abnormalities and mental retardation. In order to characterize the clinical features and disease progression of patients affected by alpha-Mannosidosis, a survey study was conducted. 43 patients from 4 European countries participated in this longitudinal study. Age range of the participants was 3 to 42 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 30 publications
6
64
0
8
Order By: Relevance
“…However, it is possible, that screening patient populations with urine oligosaccharide excretion may be more cost effective in countries without funding for exome sequencing approaches. In our study, reported clinical features in alpha‐mannosidosis were developmental delay or cognitive impairment, bone anomalies, coarse facies, hearing loss, recurrent airway infections, dysmorphism, organomegaly, hernias, ataxia, short stature, and spasticity in descending order of frequency, which corroborates and expands the data presented by Beck et al Cluster analysis enabled the mathematical distinction of five statistically similar subgroups, which clinically exhibited overlapping neurological as well as generalized disease features suggesting that pattern of clinical features and manifestations are heterogeneous and a continuous spectrum rather than well‐delineated clinical subtypes. This observation is in accordance with other lysosomal storage disorders such as free sialic acid storage disease, Farber disease or Gaucher disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible, that screening patient populations with urine oligosaccharide excretion may be more cost effective in countries without funding for exome sequencing approaches. In our study, reported clinical features in alpha‐mannosidosis were developmental delay or cognitive impairment, bone anomalies, coarse facies, hearing loss, recurrent airway infections, dysmorphism, organomegaly, hernias, ataxia, short stature, and spasticity in descending order of frequency, which corroborates and expands the data presented by Beck et al Cluster analysis enabled the mathematical distinction of five statistically similar subgroups, which clinically exhibited overlapping neurological as well as generalized disease features suggesting that pattern of clinical features and manifestations are heterogeneous and a continuous spectrum rather than well‐delineated clinical subtypes. This observation is in accordance with other lysosomal storage disorders such as free sialic acid storage disease, Farber disease or Gaucher disease …”
Section: Discussionmentioning
confidence: 99%
“…Our literature search was conducted within Pubmed and did not include other databases such as Embase, therefore we cannot exclude the possibility that published cases might be missed. Beck et al assessed 43 patients over 2 years and focused on biomarker and softer clinical endpoints . The advantage of the latter study is that it was conducted prospectively and captured quantitative outcomes and their variability over time under a single protocol in a multicenter setting.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Thus, the values given at spirometry may be inaccurate for some of the patients [17, 18] and the relationship between the FVC% and the different subgroups may be uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…General information: Rare, progressive lysosomal storage disorder due to deficiency of alpha‐mannosidase ( MAN2B1 ). Two distinct phenotypes: a severe form (type 1) with hepatomegaly and early death, and a mild form (type 2) with hearing loss, developmental delay, and slow progression with survival into adulthood . Incidence of .2 in 100,000 live births.…”
Section: Glossarymentioning
confidence: 99%